Discrimination, Assimilation, and Cultural Identity in Tahar Ben Jelloun's Leaving Tangier - Emir, Derya (European Journal of Social Science Education and Research, 2014)
In today's multicultural countries, cultural diversity, hybridity, assimilation, and cultural identity are key issues. By focusing on the problem of immigration and its inevitable traumatic results on the migrants, Tahar Ben Jelloun's Leaving Tangier fully presents Azel (the protagonist) and his acquaintances' search for identity in terms of history, religion, nationality and cultural identity. Tahar Ben Jelloun's Leaving Tangier is the story of a Moroccan brother and sister who are burning with the desire to migrate to Spain in order to attain better life. The accomplishment of their dreams actualizes at the cost of some compromises and sacrifices that end with the protagonists' physical, emotional failure, and annihilation. The winner of Prix Goncourt for La Nuit Sacrée (The Sacred Night) in 1987, a Moroccan novelist Tahar Ben Jelloun is one of the most prolific and important writers of the recent years. As a novelist and critic, Ben Jelloun artfully combines the fact and fiction, past and present, East and West in his works. in this respect, he creates multidimensional writings that can be read and interpreted from several perspectives. Tahar Ben Jelloun's Leaving Tangier (2006) presents the issues of "wounded childhood," "solitude," "displacement," and "alienation" both individually and collectively in the colonial history of Tangier. This study focuses on the issues of discrimination, assimilation, and cultural identity, experienced by the characters in the novel, resulting from the immigration of individuals from their homelands to Europe in order to find better life conditions.
Keywords: Discrimination, Assimilation, Immigration, Cultural identity, Tahar Ben Jelloun, Leaving Tangier, Postcolonial Literature.